2020
DOI: 10.1016/j.apacoust.2020.107286
|View full text |Cite
|
Sign up to set email alerts
|

Transient vibro-acoustic analysis of squeal events based on the experimental bench FIVE@ECL

Abstract: The proposed study investigates the transient and stationary non-linear vibrations and acoustic phenomena occurring during the squeal phenomenon. Experiments are performed on the test bench Friction-Induced Vibration and noisE at Ecole Centrale de Lyon (FIVE@ECL).The first major contribution of the study is to demonstrate the ability of this test bench to reproduce transient squeal events for a given operational condition, allowing to conduct a thorough and robust study on the physical understanding of transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This work was supported by Shanghai Sailing Program (21YF1449000); the National Natural Science Foundation of China (52072270). Then make use of equation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), equations (2-11)-(2-13) can be expressed in matrix form as…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This work was supported by Shanghai Sailing Program (21YF1449000); the National Natural Science Foundation of China (52072270). Then make use of equation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), equations (2-11)-(2-13) can be expressed in matrix form as…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…6,7 Stender et al 8 observed that brake squeal had multi-scale characteristics. Sinou et al [9][10][11] established a new test bench for friction induced vibration. And the correlation between sound pressure and vibration was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the study of brake squeal is a multi-physics problem that requires advanced analysis in various fields such as vibration, tribology, thermodynamics and acoustics, for example. As a result, academic test rigs [18][19][20][21][22][23][24][25][26][27] have been developed in order to propose experimental contributions in order to better understand friction-induced vibrations and noise.…”
Section: Introductionmentioning
confidence: 99%
“…joints [8,10,11], dampers and brake systems [12][13][14]. High amplitude FIV is commonly the consequences of friction instabilities that give rise to tedious noise [15][16][17][18] usually classified in squeal, groan or chatter depending on the frequency band in which it occurs [19]. One of the phenomena at the origins of such noises are stick-slip [20].…”
Section: Introductionmentioning
confidence: 99%